THE STATUS OF WOMEN DESCRIBED IN THE NOVEL “JANE EYRE” BY CHARLOTTE BRONTE (International Conference on Educational Discoveries and Humanities, 2025)
Charlotte Brontë’s Jane Eyre presents a powerful challenge to the patriarchal norms of Victorian society. Through the journey of Jane, Brontë emphasizes women’s struggle for identity, autonomy, and equality. This article explores the position of women as depicted in the novel using analysis, synthesis, induction, comparison, synecdoche, and empirical observation. By examining various female characters and their experiences, the paper highlights the social inequalities of the time and demonstrates how Jane Eyre remains a critical feminist text, relevant even in contemporary discussions of gender.